The epidemiology of suicide and suicidal behaviour across the lifespan in Nigeria: a systematic review of the literature (2021)
BACKGROUND/PURPOSE: Suicidal behaviour is a global public health issue affecting all ages, gender, and regions of the world. This systematic review sought to synthesize the available evidence on the prevalence and risk factors for suicide and suicidal behaviour across the lifespan in Nigeria. DATA SOURCE: The databases of PubMed, Embase, Medline, PsychInfo, Google Scholar and African Journals OnLine (AJOL). STUDY SELECTION: Literature on suicidal behaviour and suicide from Nigeria published between 2000 and 2019. DATA EXTRACTION: Data were extracted independently by two authors using a fixed template. RESULTS: The search identified 431 articles; 23 were eligible for inclusion. The 12-month prevalence of suicide ideation among adolescents was between 6.1–22.9% and 3–12.5% for attempts; identified risk factors were sexual abuse, family dysfunction and food insecurity. For the adult population, lifetime rates of suicidal ideation, plan and attempt were 3.2%, 1.0% and 0.7% respectively; risk factors included age (peak in the third decade of life), childhood adverse experiences and the presence of mood disorders. In the elderly the rates were 4.0% for ideation, 0.7% for plan and 0.2% for attempt. Risk factors identified in the elderly were being single (separation or widowhood) and rural residence. Suicides accounted for 0.3– 1.6% of autopsies performed by the coroners and constituted the least common cause of death. Suicides were more common in males and peaked in the third decade of life. CONCLUSION: Suicide and suicidal behaviour in the Nigerian population seem to peak in young adult life suggesting that suicide prevention initiatives should target late adolescence.